2013
DOI: 10.4172/2165-7939.1000163
|View full text |Cite
|
Sign up to set email alerts
|

The BACJACTM Interspinous Device in the Treatment of Lumbar Spine Degenerative Disorders: A Prospective Study and 2-Year Follow-Up Results

Abstract: Background: In the last two decades lumbar interspinous decompression systems have gained a wide and often uncontrolled diffusion. Such devices, usually made of titanium or PEEK (polyetheretherketone), are currently implanted in different lumbar spine degenerative disorders, and clinical indications to their use are often confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Stand-alone implant or following uni-or bilateral decompression provides mid-term relief of low-back and radicular pain, and improvement of neurogenic intermittent claudication (NIC), in the following lumbar spine disorders: central and foraminal stenosis, recurrent disc protrusion associated with foraminal stenosis, mild antero-or retrolisthesis, degenerative disc disease (DDD), synovial cysts associated with pseudospondylolisthesis. When considering these disorders, this device seems to provide a 'primary stabilizing effect'; a 2-year follow-up confirms that this effect is still active, with no need for subsequent more invasive fixation surgical procedures [3].…”
Section: Bacjac (Surgalign Usa)mentioning
confidence: 72%
See 1 more Smart Citation
“…Stand-alone implant or following uni-or bilateral decompression provides mid-term relief of low-back and radicular pain, and improvement of neurogenic intermittent claudication (NIC), in the following lumbar spine disorders: central and foraminal stenosis, recurrent disc protrusion associated with foraminal stenosis, mild antero-or retrolisthesis, degenerative disc disease (DDD), synovial cysts associated with pseudospondylolisthesis. When considering these disorders, this device seems to provide a 'primary stabilizing effect'; a 2-year follow-up confirms that this effect is still active, with no need for subsequent more invasive fixation surgical procedures [3].…”
Section: Bacjac (Surgalign Usa)mentioning
confidence: 72%
“…Biomechanical studies have shown that all of ISDs act grossly in the same way: they enlarge spinal canal dimensions, increase neuro-foramina height, reduce intradiscal pressure in neutral and extended position [2]; moreover, they have a 'primary stabilizing effect' [3]. The ISDs designed 'for fusion' additionally show to promote bone fusion at the instrumented level.…”
Section: Experimental Datamentioning
confidence: 99%